The paradigm of IL-23-independent production of IL-17F and IL-17A and their role in chronic inflammatory diseases - Navarro-Compán, Victoria; Puig, Luis; Vidal, Silvia; Ramírez, Julio; Llamas-Velasco, Mar; Fernández-Carballido, Cristina; Almodóvar, Raquel; Pinto, José Antonio; Galíndez-Aguirregoikoa, Eva; Zarco, Pedro; Joven, Beatriz; Gratacós, Jordi; et al. (Frontiers in Immunology, 2023)
Interleukin-17 family (IL-17s) comprises six structurally related members (IL-17A to IL-17F); sequence homology is highest between IL-17A and IL-17F, displaying certain overlapping functions. In general, IL-17A and IL-17F play important roles in chronic inflammation and autoimmunity, controlling bacterial and fungal infections, and signaling mainly through activation of the nuclear factor-kappa B (NF-κB) pathway. The role of IL-17A and IL-17F has been established in chronic immune-mediated inflammatory diseases (IMIDs), such as psoriasis (PsO), psoriatic arthritis (PsA), axial spondylarthritis (axSpA), hidradenitis suppurativa (HS), inflammatory bowel disease (IBD), multiple sclerosis (MS), and asthma. CD4+ helper T cells (Th17) activated by IL-23 are well-studied sources of IL-17A and IL-17F. However, other cellular subtypes can also produce IL-17A and IL-17F, including gamma delta (γδ) T cells, alpha beta (αβ) T cells, type 3 innate lymphoid cells (ILC3), natural killer T cells (NKT), or mucosal associated invariant T cells (MAIT). Interestingly, the production of IL-17A and IL-17F by innate and innate-like lymphocytes can take place in an IL-23 independent manner in addition to IL-23 classical pathway. This would explain the limitations of the inhibition of IL-23 in the treatment of patients with certain rheumatic immune-mediated conditions such as axSpA. Despite their coincident functions, IL-17A and IL-17F contribute independently to chronic tissue inflammation having somehow non-redundant roles. Although IL-17A has been more widely studied, both IL-17A and IL-17F are overexpressed in PsO, PsA, axSpA and HS. Therefore, dual inhibition of IL-17A and IL-17F could provide better outcomes than IL-23 or IL-17A blockade.